Molecular epidemiology of OXA‐48‐producing Klebsiella pneumoniae in France. (29th July 2014) - Liapis, E.; Pantel, A.; Robert, J.; Nicolas‐Chanoine, M.‐H.; Cavalié, L.; van der Mee‐Marquet, N.; de Champs, C.; Aissa, N.; Eloy, C.; Blanc, V.; Guyeux, C.; Hocquet, D.; et al.
Abstract We characterized 53 OXA‐48‐producing Klebsiella pneumoniae (OXA‐48‐Kp) isolated between 2011 and 2013 in 21 French hospitals. All the isolates were genotyped using MLST and PFGE and the population structure of the species was determined by a nucleotide‐based analysis of the entire K. pneumoniae MLST database. Most of the OXA‐48‐Kp isolates also produced CTX‐M‐15 and remained susceptible to imipenem and meropenem. The isolates were distributed into 20 STs, of which five were dominant (ST15, ST101, ST147, ST395 and ST405). All the OXA‐48‐Kp clustered in the major clade of K. pneumoniae KpI.